Click, Trust, Buy: How Digital Signals Override Rationality in Student E-Commerce Choices on Shopee: Klik, Percaya, Beli: Bagaimana Sinyal Digital Menggantikan Rasionalitas dalam Pilihan E-Commerce Mahasiswa di Shopee - Misti Hariasih (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
Purchasing decisions are a critical factor influencing consumer behaviour in digital marketplaces, particularly on platforms like Shopee. This study examines the influence of digital marketing, marketing communication, and product quality on purchasing decisions among students of Muhammadiyah University of Sidoarjo on the Shopee e-commerce platform. The research applies a quantitative approach, with data collected through an online questionnaire distributed via Google Forms. In this study, the population targeted by the researcher is students of the Management Study Program at Universitas Muhammadiyah Sidoarjo, with a total of 1,550 students, based on data obtained from the Academic Directorate of Universitas Muhammadiyah Sidoarjo. The sample consisted of 100 respondents, determined using the Slovin formula and selected using purposive sampling, with the criteria that respondents were students who had experience purchasing products through Shopee. The collected data were analysed using multiple linear regression with the assistance of SPSS version 25, preceded by validity, reliability, and classical assumption tests to ensure the accuracy and reliability of the regression model. The findings indicate that Digital Marketing, marketing communication, and product quality have a significant influence on students’ purchasing decisions on the Shopee platform. Effective Digital Marketing strategies and clear marketing communication play an important role in shaping consumer perceptions and encouraging purchase intentions.